2017
DOI: 10.3892/mmr.2017.7599
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is activated to protect renal tubular epithelial cells against iodinated contrast media-induced cytotoxicity

Abstract: With the steady increase in the use of various contrast‑related technologies in recent years, contrast‑induced nephropathy has received significant attention from clinicians and researchers. The present study aimed to determine the potential role of autophagy in iodinated contrast media (CM)‑induced cell injury and apoptosis in human proximal renal tubular epithelial HK‑2 cells. The present study used the iodinated CM iohexol (200 mg iodine/ml) to treat HK‑2 cells for 6 h, in order to establish a damaged cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Iodinated radiographic contrast media also increased cytotoxicity in human proximal renal tubular epithelial cells [ 32 , 33 ]. Other authors showed that iodinated radiographic contrast media caused severe and prolonged oxidative stress in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Iodinated radiographic contrast media also increased cytotoxicity in human proximal renal tubular epithelial cells [ 32 , 33 ]. Other authors showed that iodinated radiographic contrast media caused severe and prolonged oxidative stress in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In order to induce a more significant profibrotic effect, high concentration of TGF-β(50 ng/ml) and high glucose (30 mM) stimulation were used to mimic diabetic renal tubular cell injury status in our study. Briefly, HK-2 cells were randomly divided into several groups: control group: d -glucose 5 mM, high glucose (30 mM) and TGF-β(50 ng/ml) intervention group, high glucose and TGF-βwith or without other interventions: paricalcitol (200 nM), 3-MA (5 mM) for indicated time (72 h) based on previous studies [ 15 , 16 ]. Furthermore, HK-2 cells were pretransfected with VDR overexpression plasmid, VDR siRNA or Mfn2 siRNA for gene disruption.…”
Section: Methodsmentioning
confidence: 99%